Evaluating the impact of a 15‐year academic partnership to promote sustainable engagement, education, and scholarship in global health. Issue 5 (21st May 2020) - Karwa, Rakhi; Miller, Monica L.; Schellhase, Ellen; Tran, Dan; Manji, Imran; Njuguna, Benson; Fletcher, Sara; Kanyi, John; Maina, Mercy; Jakait, Beatrice; Kigen, Gabriel; Kipyegon, Victor; et al.
Abstract: Introduction: In 2003, Purdue University College of Pharmacy (PUCOP) in West Lafayette, Indiana, began the Purdue Kenya Partnership (PKP) in collaboration with the Academic Model Providing Access to Healthcare, Moi University, and Moi Teaching and Referral Hospital, in Eldoret, Kenya. PUCOP's involvement utilized a tripartite approach of engagement, education, and scholarship to provide and expand sustainable access to high quality care. Objective: This paper discusses outcomes and impacts of this academic partnership. Methods: Purdue Kenya Partnership's progress in achieving its stated mission was evaluated using an outcome‐approach logic model. This model highlighted inputs, activities, and results which encompassed outputs, outcomes, and impact. A comprehensive set of ratios were calculated to quantify annual change in PKP investments against estimated metrics for engagement, education, and scholarship. These metrics were weighted by involvement level and pharmacist effort in various clinical domains. Descriptive statistics were completed that identified cumulative and totals per year for each collected data type of data collected. Results: Purdue Kenya Partnership implementation utilized initial inputs of human resources, financial capital, and strategic partnerships. These inputs supported pharmacy involvement in 16 distinct care programs in both inpatient and outpatient settings which supported the care of 457 833 individual patients and grown a clinical pharmacy staff from 0 to 22 practicing clinical pharmacists. Five unique educational programs have been established which have graduated 457 trainees. Purdue Kenya Partnership has generated over $6.2 million in grant funding and disseminated 302 peer reviewed manuscripts, posters, and oral presentations combined. Ratios describing trends in engagement, education, and scholarship as a result of using the locally focused PKP approach highlight higher initial costs compared with much lower costs per outcome several years into the partnership. Conclusion: The PKP's global health approach of prioritizing the population's care needs ("leading with care") has enabled the development of sustainable engagement, education, and scholarship infrastructure with significant gains in all three domains.